Review of approaches to improving the reliability and efficiency of technical operation of motor vehicles, taking into account the validity of engineering solutions - V.V. Krivda; O.P. Sakno; K.I. Kornilenko; S.P. Chuiko; V.P. Shumliakivskyi (Технічна інженерія)
The article presents an overview analysis of approaches to ensuring the reliability and efficiency of technical operation of motor vehicles through the implementation of engineering solutions considered as an element of a controlled dynamic system. Reliability management is based on system analysis of vulnerable components, application of methods for assessing reliability, checking and predicting technical condition. Special attention is paid to the problem of predicting failures under operating conditions in order to minimize costs. Calculations are summarized and aimed at minimizing the costs associated with the operation of motor vehicles. The study analyzes the basics of reliability, heat transfer in power plants, maintenance systems, feasibility studies of engineering solutions, as well as mathematical methods for analyzing the operational properties of cars, as well as the use of mathematical methods for analyzing the operational properties of vehicles. The role of technological processes, automation and methodological foundations for improving service efficiency is emphasized. In the context of technical operation of motor vehicles, engineering solutions provide for the development and implementation of technical, technological and organizational measures aimed at improving reliability, reducing costs and environmental burden. Improving reliability at the design and modernization stage is ensured by the durability and maintainability of structures. The applied system approach combines process modeling and the use of technical and economic analysis tools.